Dating Patterns of Young Adults during Navratri Festival of India in the City of Surat - Keshvi Chauhan; RK Bansal (Medsci Publications, 2019)
Surat is a highly urbanized and cosmopolitan city of the tradi- tional state of Gujarat. The festival of Navratri provided us with the unique opportunity to study for the variables having a signifi- cant impact on dating especially amongst the collegaites. This study was carried among 133 young adults for  understanding  their dating patterns during Navratri festival of India in the city of Surat of District Gujarat. It needs mention that dating is gradually gaining momentum in India especially among the young adults more so during socially acceptable events as Navratri. Newspa- pers have reported of increase abortions following this event pointing to the need for our interventions for safer sexual prac- tices. Scant medical literature is found pertaining to Navratri and dating hence this preliminary study.